Achieving ideal career: improving student's career self efficacy through career counseling sessions based on H.B Gelatt's decision theory - Chudari, Ima Ni'mah; Mashudi, Esya Anesty; Fatihaturosyidah, Fatihaturosyidah (ProGCouns: Journal of Professionals in Guidance and Counseling, 2020)
After successfully compiling a good career plan related to their professional work in the future, students are expected to realize these career plans successfully. For this reason, students need to be equipped with other abilities in the form of self-efficacy or the ability to believe that the efforts made will produce results and goals that are expected to be achieved. Therefore, through appropriate career counseling intervention, the self-efficacy of students in achieving an ideal career is expected to increase. This study aims to examine effectiveness of career counseling based on H.B Gelatt's decision theory to improve student self-efficacy in achieving an ideal career. This study uses quasi-experimental methods. The research subjects were third years students in UPI Serang. The research instrument used was a student self-efficacy scale and a daily reflective journal. Data analysis techniques used statistical testing in the form of percentages, central symptom measures, and two-tier test (t-test). The results showed that students' self-efficacy related to achieving an ideal career in general was in the medium category with a percentage of 50.72%. The counseling intervention program is based on the career decision making steps of Gelatt. Paired t-test results of pre-test and post-test of the experimental group showed that t arithmetic = 10.221> (greater) than t table = 2.401, testing was carried out at a = 0.05 and df = 39, meaning H1 was accepted and H0 was rejected. Thus, there is a significant difference between self-efficacy related to achieving the ideal career of students who are members of the experimental group before and after receiving treatment. Decision-making skills in particular are very influential on improving the level dimension in student self-efficacy related to achieving an ideal career.